A Review of Mongolian Cultural Integration in Urban Square Design - Jieqiong, Jiao; Malek, Nurhayati Abdul (Journal of Posthumanism, 2025)
Baotou’s urban public spaces have not naturally incorporated Mongolian cultural elements, leading to diminished local cultural identity and disconnection in public space. Surface symbolism, uneven design approaches, and a lack of cultural sustainability lead to fewer user interactions and cultural distance. This review explains how Mongolian aspects of culture can be integrated into urban square spaces through Cultural Identity Theory (CIT) and Theory of Planned Behavior (TPB) to observe user behavior, cultural identification, and emotional states in these areas. This study integrates research on cultural identity, urban planning, and behavioral psychology through a systematic literature review. Academic databases were used to search for pertinent literature on psychological and cultural determinants like emotional response, cultural affiliation, and perceived control of behavior. The thematic synthesis approach was employed to analyze how these determinants influence user engagement in culturally diverse urban environments. Evidence indicates that perceived behavioral control, cultural identity, and emotional response are key predictors of user engagement in Mongolian-themed urban public space. Authenticity is most important because superficial cultural representation does not result in cultural attachment. Research also indicates that integrating tradition and modernity enhances sustainability and usability, providing learning points for urban planners to create culturally attractive public spaces. This paper captures the significance of genuine cultural representation in stimulating engagement and preserving local identity in urban planning.